"Unmute" Bread: Listening, Improvising, and Performing with Sourdough in Quarantine - Galloway, Kate; Fuller, Rachael (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
While many of our colleagues are avidly baking and feeding their newly acquired sourdough starters while sheltering in place during the COVID-19 pandemic, we are conducting ethnographic work with individuals who have embraced the stylistics and aesthetics of improvisation in acts of caring for, listening to, baking with, and recording their sourdough starters, as well as performing alongside their bread-kin. Imagine, in some instances, the multispecies improvisational style of David Rothenberg’s co-performance with birds, whales, and insects (Rothenberg 2017; 2016; 2002; Ryan 2020), but with wild yeast and freshly baked bread. In this article we ask: What is it about the conditions of sheltering in place, quarantine, and domestic isolation that fosters an experimental space for reconfiguring multispecies improvisation and performance to include our foodways? Why has baking, specifically bread (and sourdough), rather than other forms of domestic activity and craft fostered this specific sonic response during these pandemic times? How are participants sharing, scrolling through, and listening to these domestic performances across social media? What does the sonic register of these multimodal texts communicate to other socially distancing social media users? Through ethnographic fieldwork of performing with, listening to, musicalizing, and caring for sourdough starters, their “screaming yeast” (Roosth 2009), and the baked result, this article places improvisation studies, domestic practices, multispecies performance, gastromusicology, and pandemic spatial conditions in dialogue to address these questions.